Mediterranean diet adherence in 9-years old children: a cross-sectional study in the part of the Split-Dalmatia County, Croatia - Tomelić Ercegović, Katarina; Đolonga, Petar; Družianić, Zvonimir; Ercegović, Vladimir; Karin, Željka (Central European journal of public health, 2024)
OBJECTIVES: Childhood obesity is a growing global problem that can be prevented by improving diet quality. Mediterranean diet (MedDiet), historically present in Mediterranean countries, is considered one of the healthiest dietary patterns. This cross-sectional study aimed to determine the MedDiet adherence and anthropometric parameters in 9-year-old children from the central geographic locations of Split-Dalmatia County, Croatia. METHODS: The study analysed data obtained from 158 children aged nine years from central parts of Dalmatia: Split and Hvar. To assess the MedDiet adherence, the parents of the children filled out the Mediterranean Diet Index (KIDMED) questionnaire. Appointed school medicine specialists collected anthropometric data of the children and categorized them into body mass index (BMI) categories according to the Center for Disease Control and Prevention (CDC) criteria. Additionally, we assessed the influence of parents' education degree on children's MedDiet adherence and anthropometric measures. RESULTS: Results showed that more than a quarter of nine-year-olds included in this study were overweight or obese (BMI ≥ 85th percentile for age and sex). One of the main findings was that 72% of children had suboptimal (poor or average) MedDiet adherence. Moreover, children with suboptimal KIDMED results (KI < 8) had significantly higher body weight, waist circumference, hip circumference, and waist-to-height ratio. Also, results showed that mothers' education notably influences children's anthropometry. CONCLUSION: Our study found that childhood obesity is a significant concern among 9-year-olds, with a high prevalence of overweight and obesity. Additionally, our results showed that MedDiet adherence is suboptimal among this age group. These results indicate that children of the Mediterranean are not spared of modern life challenges. This problem should be prioritized in the future to prevent the development of a metabolically compromised adult population.
Keywords: index tělesné hmotnosti; Cross-Sectional Studies; Croatia; Diet, Mediterranean; průzkumy a dotazníky; mužské pohlaví; průřezové studie; Pediatric Obesity; Chorvatsko; Body Mass Index; dítě; Child; ženské pohlaví; Anthropometry; Humans; Surveys and Questionnaires; antropometrie; strava středomořská; Female; obezita dětí a dospívajících; lidé; Male